Offshoring strategies : evolving captive center models - Oshri, Ilan (MIT Press, 2011)
From the publisher. In today's globalized economy, firms often consider offshoring when confronted by rising costs and fierce competition. One mode of offshoring has continued to grow despite the current global economic turmoil: the captive center. Captive centers are offshore subsidiaries or branch offices that provide the parent company with services, usually in the form of back-office activities. Oshri examines the evolution of the captive center. He identifies basic captive center models, examines the captive center strategies pursued by Fortune Global 250 firms, describes current captive center trends, and offers detailed individual case studies that illustrate each model. His analysis highlights the strategic paths available to firms that want to maximize the returns offered by captive centers. Oshri outlines six models for captive centers that range from the basic wholly owned branch office to hybrids and joint ventures and identifies evolutionary paths along which the basic model develops. He analyzes firms' strategies during initial set-up, then tracks the changes as strategies evolve to meet different business needs. The case studies, all based on the Fortune Global 250, include the development of a basic captive unit into a complex hybrid structure; the evolution of a captive center into a shared service center offering services to other international firms; the divestment of a captive center to a private equity firm; and the migration of a captive center to a location where costs were lower.